Application of linear body measurements for predicting live weight in Ouled Djellal breed - DJAOUT, A; AFRI-BOUZEBDA, F; BOUZEBDA, Z; BENIDIR, M; BELKHIRI, Y (The Indian Journal of Animal Sciences, 2018)
The objective of this study was to predict the body weight of 66 females and 15 males Ouled Djellal breed aged over 2 years using fourteen simple linear body measurements and CREVAT formula. The total body length (TBDL), body length (BDL), scapular-ischial length (SIL), withers height (WH), heart girth (HG), chest depth (CD), paunch girth (PG), shoulder width (SW), hip-width (HW), trochanter width (TW), ischia width (IW), pelvis length (PL), cannon length (CL) and cannon perimeter (CP) were measured in centimeters, and body weight (BW) was determined in kilogram using a weighing scale. Results of the correlation coefficient showed that heart girth and the withers height were highly correlated with body weight (r = 0.93 and r =0.91 respectively), with variations by sex. Results of the stepwise regression showed that heart girth (HG), withers height (WH), scapular-ischiallength (SIL) and thecannon perimeter (CP) are the best prediction parameters of body weight in animals studied. From the CREVAT formula, the body weight was estimated by the HG (in meters): BW = 57.9 HG3. According to the different statistical methods used and the formula of CREVAT, we can conclude that body weight in Ouled Djellal breed can be estimated using simple linear body measurement of heart girth.